Left posterior temporal cortex is sensitive to syntax within conceptually matched Arabic expressions - Suhail Matar (Nature Portfolio, 2021)
Abstract During language comprehension, the brain processes not only word meanings, but also the grammatical structure—the “syntax”—that strings words into phrases and sentences. Yet the neural basis of syntax remains contentious, partly due to the elusiveness of experimental designs that vary structure independently of meaning-related variables. Here, we exploit Arabic’s grammatical properties, which enable such a design. We collected magnetoencephalography (MEG) data while participants read the same noun-adjective expressions with zero, one, or two contiguously-written definite articles (e.g., ‘chair purple’; ‘the-chair purple’; ‘the-chair the-purple’), representing equivalent concepts, but with different levels of syntactic complexity (respectively, indefinite phrases: ‘a purple chair’; sentences: ‘The chair is purple.’; definite phrases: ‘the purple chair’). We expected regions processing syntax to respond differently to simple versus complex structures. Single-word controls (‘chair’/‘purple’) addressed definiteness-based accounts. In noun-adjective expressions, syntactic complexity only modulated activity in the left posterior temporal lobe (LPTL), ~ 300 ms after each word’s onset: indefinite phrases induced more MEG-measured positive activity. The effects disappeared in single-word tokens, ruling out non-syntactic interpretations. In contrast, left anterior temporal lobe (LATL) activation was driven by meaning. Overall, the results support models implicating the LPTL in structure building and the LATL in early stages of conceptual combination.